Noninvasive Transdermal Delivery System of Lidocaine Using an Acoustic Droplet‐Vaporization Based Wearable Patch. Issue 49 (17th October 2018) - Soto, Fernando; Jeerapan, Itthipon; Silva‐López, Cristian; Lopez‐Ramirez, Miguel Angel; Chai, Ingrid; Xiaolong, Lu; Lv, Jian; Kurniawan, Jonas F.; Martin, Ian; Chakravarthy, Krishnan; Wang, Joseph
Abstract: Current technologies for managing acute and chronic pain have focused on reducing the time required for achieving high therapeutic efficiency. Herein a wearable transdermal patch is introduced, employing an acoustic droplet vaporization (ADV) methodology, as an effective noninvasive transdermal platform, for a fast local delivery of the anesthetic agent lidocaine. The skin‐worn patch consists of a flexible drug reservoir containing hundreds of micropores loaded with lidocaine, and mixed with the perfluorocarbon (PFC) emulsion. The ultrasound‐triggered vaporization of the PFC emulsion provides the necessary force to breach dermal barriers. The drug release kinetics of our model was investigated by measuring the amount of lidocaine that passed through phantom tissue and pigskin barriers. The ADV platform increases the payload skin penetration resulting in shorter treatment times compared to passive diffusion or ultrasound alone, holding considerable promise for addressing the delayed therapeutic action and slow pain relief of existing delivery protocols. It is envisioned that the integration of ADV‐based transdermal devices could be expanded to the depth‐dependent delivery of other pain management, vaccines, and gene therapy modalities. Abstract : A noninvasive wearable transdermal patch for effective and rapid local delivery of the anesthetic agent lidocaine is described. The ultrasound acoustic droplet vaporization delivery mechanism provides large force toward enhanced skin penetration and faster pain relief.